Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am struggling to justify the the consistency of algebraic definition of vector products.

Say given Two vector A , B

A.B = |A|. |B| cos(0)

where Lets assume

A is represented by (x1,y1) 
B is represented by (x2,y2)
|A| = sqrt(x1^2 + y1^2)
|B| = sqrt(x2^2 + y2^2)

so by Algebraic definition of dot product

A.B = x1.x2 + y1.y2


cos(0) = A.B / (sqrt(x1^2 + y1^2) * sqrt(x2^2 + y2^2))

which is equivalent to

  cos(0) =  (x1.x2 + y1.y2) / (sqrt(x1^2 + y1^2) *  sqrt(x2^2 + y2^2))

if two vector are parallel

cos(0) should be one 1

for two parallel vectors ratio same ratio (which essentially is the slope in 2D ) x1/y1 == x2/y2

So for two parallel vector how to you prove

(x1.x2 + y1.y2) / (sqrt(x1^2 + y1^2) +  sqrt(x2^2 + y2^2)) equals to 1

x1/y1 == x2/y2
share|cite|improve this question
Do you mean |B| = sqrt(x2^2 + y2^2)? $\;$ – Ricky Demer Sep 9 '13 at 22:55
@Rick Yes. i am representing the vector B as (x2,y2) – David Sep 9 '13 at 22:56
@Rick Fixed the typo. – David Sep 9 '13 at 22:57
@David The $+$ sign in the denominator connecting two square roots should be multiplication. – Tunococ Sep 10 '13 at 0:25
up vote 1 down vote accepted

You turned the product of $|A|$ and $|B|$ into a sum of the square roots. Replacing with the original product, you get this:

There is a number $k$ such that $y_1=kx_1$ and $y_2=kx_2$, since $x=x_1/y_1=x_2/y_2$.

Now your big expression is equal to $\frac{x_1x_2+k^2x_1x_2}{\sqrt{x_1^2+k^2x_1^2}\sqrt{x_2^2+k^2x_2^2}}=\frac{(1+k^2)x_1x_2}{|x_1|\sqrt{1+k^2}|x_2|\sqrt{1+k^2}}=\frac{x_1x_2}{|x_1x_2|}$.

Notice that you get $1$ or $-1$, which is normal, because your assumption $x_1/y_1=x_2/y_2$ does not imply that the two vectors have the same direction: they can be opposite.

share|cite|improve this answer

\begin{align} \frac{x_1 x_2 + y_1 y_2}{\sqrt{x_1^2 + y_1^2}\sqrt{x_2^2 + y_2^2}} = \frac{\frac{x_1}{y_1}\frac{x_2}{y_2} + 1}{\sqrt{\left(\frac{x_1}{y_1}\right)^2 + 1}\sqrt{\left(\frac{x_2}{y_2}\right)^2 + 1}} = \frac{\left(\frac{x_1}{y_1}\right)^2 + 1}{\sqrt{\left(\frac{x_1}{y_1}\right)^2 + 1}\sqrt{\left(\frac{x_1}{y_1}\right)^2 + 1}} = 1 \end{align}

share|cite|improve this answer

If two non-zero vectors $A,B$ are parallel, then there is some constant $\lambda$ such that $A=\lambda B$.

Then $\cos \theta = \frac{A \cdot B}{\|A\| \|B\|} = \frac{\lambda B \cdot B}{|\lambda|\|B\| \|B\|} = \frac{\lambda}{|\lambda|} \frac{\|B\|^2}{\|B\|^2} = \operatorname{sgn} \lambda$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.